Study of Welding Process towards Crevice Corrosion Resistance on UNS N06625 Material According to ASTM G 48 D - Bastara Putra, Nugraha
Equipment in oil and gas industries and petrochemical industries have specifications that require a material that has high corrosion resistance. In the construction of machinery, there is a complex construction that requires the process of grafting 2 materials. Generally, the connection process is done by welding process. However, many problems are found in the connection part. One of them is the occurrence of corrosion phenomena that cause damage and deterioration. These problems can be answered with the selection of materials that have the appropriate specifications. One material with appropriate specifications is UNS N06625 material. Material UNS N06625 has high corrosion resistance properties. Due to the complex construction, therefore the welding process is done to meet the specifications of the construction. Material UNS N06625 has a good weldability but when there is a solidification process then there will be changes, one of them is the decrease in corrosion resistance by material UNS N06625. This research was conducted to see the change of corrosion resistance properties through Critical Crevice Temperature (CCT). This research begins with characterization using Energy Dispersive Spetroscopy (EDS) to ensure the test specimens are UNS N06625. The next process is to conduct welding simulation with Tungsten Arc Welding (GTAW) method with heat input of 0.39 kJ / mm to 4 test specimens. The determination of the theoretical CCT value based on the composition refers to ASTM G 48 D. After welding, to see and prove the difference of structure after solidification, metallography and hardness testing by microvickers method. Corrosion testing was performed with immersion for 72 hours at 35, 25, 20, and 15 0C temperature using a mixture of FeCl3, HCL, and aqua dm. Immersion results do not indicate the occurrence of defects at temperatures 15, 20, and 25 0C, so that changes in CCT values can only be approached qualitatively. The value of CCT with qualitative methods is estimated to be in the range 25 - 35 0C.